2021
DOI: 10.1002/acn3.51410
|View full text |Cite
|
Sign up to set email alerts
|

Home infusions of natalizumab for people with multiple sclerosis: a pilot randomised crossover trial

Abstract: Objective The delivery of healthcare at home has expanded to intravenous infusions of monoclonal antibodies. A recently developed model of care for home infusions of natalizumab for people with relapsing‐remitting multiple sclerosis was evaluated. This pilot study of home infusions of natalizumab and usual care (attendance in a hospital out‐patients’ clinic) compared safety, feasibility, patient satisfaction, effectiveness and costs. Methods In this randomised AB/BA crossover trial, 37 adults were randomised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…In a pilot crossover clinical study, patients with MS were randomized to receive usual care or home infusions of natalizumab, and were then switched to receive the alternate treatment. 27 No AEs were recorded in the crossover pilot study of natalizumab treatment, and no differences were found between adherence or infection rates between settings. Significantly greater satisfaction with convenience was found with home infusions, and costs were reduced compared with infusions received in clinical settings.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a pilot crossover clinical study, patients with MS were randomized to receive usual care or home infusions of natalizumab, and were then switched to receive the alternate treatment. 27 No AEs were recorded in the crossover pilot study of natalizumab treatment, and no differences were found between adherence or infection rates between settings. Significantly greater satisfaction with convenience was found with home infusions, and costs were reduced compared with infusions received in clinical settings.…”
Section: Discussionmentioning
confidence: 95%
“…It is important to note that available studies in other DMTs and antibiotic treatment administration have shown comparable safety and efficacy with at‐home treatments compared with standard clinical settings. In a pilot crossover clinical study, patients with MS were randomized to receive usual care or home infusions of natalizumab, and were then switched to receive the alternate treatment 27 . No AEs were recorded in the crossover pilot study of natalizumab treatment, and no differences were found between adherence or infection rates between settings.…”
Section: Discussionmentioning
confidence: 99%
“…To optimize satisfaction and quality of life with intravenous mAb treatments and to improve healthcare institutional resource utilization in MS, efforts are made to support home-based and outpatient infusion management (Vijayan et al 2017 ; Schultz et al 2021 ; Barrera et al 2022 ; Räuber et al 2022 ). It was found that people are generally open to receiving the intravenous treatment at home and that supporting health services need to ensure safety and be efficient, responsive, and flexible.…”
Section: Key Developments In Providing Customer-centric Product Prese...mentioning
confidence: 99%
“…91 748 of July 31, 1991, and depends on dedicated medical and paramedical teams in a given area. Beyond the context of the pandemic and the need to ensure the continued treatment of these patients (risk of rebound when natalizumab is stopped) ( O'Connor et al., 2011 ), the decision of the HAS was based on a few previous experiences, particularly in Australia, reporting encouraging results for safety, efficacy, and patient satisfaction ( Vijayan et al., 2017 ; Schultz et al., 2019 ; Juaton et al., 2020 ; Schultz et al., 2021 ). Indeed, it is essential to take the patients’ viewpoint into account (in addition to the clinical criteria of efficacy and safety) when implementing of new modes of organization for their care ( Committee on Quality of Health Care in America ; Carman et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%